2019
DOI: 10.1186/s12934-019-1127-8
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the biosynthesis of betulinic acid and related triterpenoids in Yarrowia lipolytica via multimodular metabolic engineering

Abstract: Background: Betulinic acid is a pentacyclic lupane-type triterpenoid and a potential antiviral and antitumor drug, but the amount of betulinic acid in plants is low and cannot meet the demand for this compound. Yarrowia lipolytica, as an oleaginous yeast, is a promising microbial cell factory for the production of highly hydrophobic compounds due to the ability of this organism to accumulate large amounts of lipids that can store hydrophobic products and supply sufficient precursors for terpene synthesis. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 68 publications
2
84
0
Order By: Relevance
“…In order to improve lupeol production, we first up-regulated the mevalonate pathway by overexpressing the rate-limiting enzyme HMG1 (3-hydroxy-3-methylglutaryl coenzyme A reductase) [29] in strain LU-9, generating strain LU-10. It has been reported that synchronous overexpression of ERG1 (squalene synthase) and ERG9 (squalene monooxygenase) [30] exhibited cooperativity towards enhancing terpenes synthesis [22]. Hence, we further performed this combination based on the HMG1 overexpression to generate strain LU-11.…”
Section: Engineering Of Mva and Lipid Metabolism To Improve Lupeol Prmentioning
confidence: 99%
“…In order to improve lupeol production, we first up-regulated the mevalonate pathway by overexpressing the rate-limiting enzyme HMG1 (3-hydroxy-3-methylglutaryl coenzyme A reductase) [29] in strain LU-9, generating strain LU-10. It has been reported that synchronous overexpression of ERG1 (squalene synthase) and ERG9 (squalene monooxygenase) [30] exhibited cooperativity towards enhancing terpenes synthesis [22]. Hence, we further performed this combination based on the HMG1 overexpression to generate strain LU-11.…”
Section: Engineering Of Mva and Lipid Metabolism To Improve Lupeol Prmentioning
confidence: 99%
“…The lipogenic acetyl-CoA and malonyl-CoA flux have been repurposed for production of β-carotenoids (Gao, Tong et al 2017, Larroude, Celinska et al 2018, polyketides (Markham, Palmer et al 2018, Liu, Marsafari et al 2019, Lv, Marsafari et al 2019, Palmer, Miller et al 2020, and terpenoids (Jin, Zhang et al 2019 in Yarrowia lipolytica. However, substantial portion of acetyl-CoA and malonyl-CoA is channeled into lipid synthesis in the engineered strains.…”
Section: Introductionmentioning
confidence: 99%
“…Yarrowia lipolytica is an industrial oleaginous yeast that has been extensively engineered to synthesize lipophilic compounds, including lipids (Qiao, Wasylenko, Zhou, Xu, & Stephanopoulos, 2017), oleochemicals (P. Xu, Qiao, Ahn, & Stephanopoulos, 2016), carotenoids (Gao et al, 2017;Macarena Larroude et al, 2018), terpenoids (Jin, Zhang, Song, & Cao, 2019) and aromatic polyketides (Lv, Marsafari, Koffas, Zhou, & Xu, 2019) et al The lipogeneity of this yeast makes it a superior host to produce chemicals that are derived from acetyl-CoA, malonyl-CoA, HMG-CoA and NADPHs. The compartmentalization of oil droplets into lipid bodies provides a hydrophobic environment to sequestrate many lipid-related compounds and mitigate the toxicity issues associated with lipophilic membrane damages.…”
Section: Introductionmentioning
confidence: 99%
“…A large collection of customized genetic toolboxes, including YaliBricks gene assembly (Wong, Engel, Jin, Holdridge, & Xu, 2017), CRISPR-Cas9 (Bae, Park, Kim, & Hahn, 2020;Macarena Larroude, Trabelsi, Nicaud, & Rossignol, 2020) or CRISPR-Cpf1 (Yang, Edwards, & Xu, 2020) genome editing, Cre-LoxP-based iterative chromosomal integrations (Lv, Edwards, Zhou, & Xu, 2019), transposon-based mutagenesis (Wagner, Williams, & Alper, 2018) and Golden-gate cloning (Celińska et al, 2017;Egermeier, Sauer, & Marx, 2019;M. Larroude et al, 2019), enabled us to rapidly modify its genome and evaluate many metabolic events to explore the catalytic diversity of this yeast beyond its regular portfolio of fatty acids, fatty alcohols, biofuels et al Recent metabolic engineering effort in this yeast has allowed us to access more specialized secondary metabolites with pharmaceutical values, including sesquiterpenes (Marsafari & Xu, 2020), triterpenoids (Jin et al, 2019) and flavonoids (Lv, Marsafari, et al, 2019;Palmer, Miller, Nguyen, & Alper, 2020) et al Isoprenoids are a large group of natural products with diverse biological functions. An estimation of more than 70,000 isoprenoids, ranging from monoterpenes, sesquiterpenes, diterpenes and triterpenes have been discovered from nature (Moser & Pichler, 2019).…”
Section: Introductionmentioning
confidence: 99%